STRATEGI PENGUATAN IDENTITAS KULINER LOKAL: PELATIHAN PENGEMASAN DAN PEMASARAN PALLU BASA BARRU SEBAGAI DAYA TARIK WISATA KULINER DAERAH - Hartati; Nur Hikmah; La Baba (STKIP Subang, 2025)
This study aims to analyze the effectiveness of strategies to strengthen the identity of local culinary products, namely Pallu Basa Barru, through integrated training in packaging and digital marketing to increase its attractiveness as a regional culinary tourism destination. The method used was Participatory Action Research (PAR) with a qualitative-descriptive approach, involving Pallu Basa culinary MSMEs in Barru Regency, South Sulawesi. Data were collected through observation, in-depth interviews, and documentation of training outcomes. The results showed that interventions in visual branding, packaging innovation (instant products), and the adoption of digital marketing (social media and e-commerce) significantly strengthened Pallu Basa's image as a distinctive product. This identity strengthening not only increased the average partner's turnover by 40% in three months but also expanded market reach beyond Sulawesi. The study concluded that combining authentic culinary preservation with modernized packaging and digital marketing strategies is key to transforming local culinary products into high-value tourism assets.